2006
DOI: 10.1002/chin.200616260
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro and in vivo Antitumor Activity of Vitamin C: K3 Combinations Against Prostate Cancer

Abstract: Organic chemistry Z 0200The in vitro and in vivo Antitumor Activity of Vitamin C: K3 Combinations Against Prostate Cancer -[191 refs.]. -(JAMISON, J. M.; GILLOTEAUX, J.; TAPER, H. S.; CALDERON, P. B.; PERLAKY, L.; THIRY, M.; NEAL, D. R.; BLANK, J. L.; CLEMENTS, R. J.; GETCH, S.; et al.; Horizons Cancer Res. 7 (2005) 189-236; Dep. Urol., Summa Health Syst., Northeastern Ohio Univ., Akron, OH 44325, USA; Eng.) -Lindner 16-260

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 131 publications
3
23
0
Order By: Relevance
“…Electrophoresis of DNA revealed a spread pattern. These results in conjunction with previous studies (Buc Calderon et al, 2003;Verrax et al, 2003Verrax et al, , 2004Jamison et al, 2005) suggested that Ca 2ϩ disregulation and cell acidification led to the caspase-3-independent serial reactivation of DNase I and DNase II and the degradation of T24 cell DNA ).…”
Section: Cytotoxicity Of Vc:vk 3 Combinationsupporting
confidence: 86%
See 4 more Smart Citations
“…Electrophoresis of DNA revealed a spread pattern. These results in conjunction with previous studies (Buc Calderon et al, 2003;Verrax et al, 2003Verrax et al, , 2004Jamison et al, 2005) suggested that Ca 2ϩ disregulation and cell acidification led to the caspase-3-independent serial reactivation of DNase I and DNase II and the degradation of T24 cell DNA ).…”
Section: Cytotoxicity Of Vc:vk 3 Combinationsupporting
confidence: 86%
“…The few mitochondria observed distally, near the self-excision zone, were only swollen. In summary, menadione-induced actions are rapid and involve depletion of reduced thiols, Ca 2ϩ disregulation, and caspase-3-independent reactivation of DNase I within the first hour of treatment Jamison et al, 2005). This subsequent DNA degradation is consistent with the decreased optical density of Feulgen staining (Fig.…”
Section: Menadione Cytotoxicitysupporting
confidence: 65%
See 3 more Smart Citations